Peran Gaya Kepemimpinan Jalur Tujuan (Path-Goal) Pada Peningkatan Kinerja Guru Sekolah: Studi Kasus Di SMAN 1 Patianworo - Ika Nurillah Ati; Nuril Fitria; Arista Maulida Roziana Putri; Muhammad Arung Nazarudin; Mochammad Isa Anshori (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the role of path-goal leadership style in improving the performance of school teachers in the mentioned school. The expected outcome of implementing the path-goal leadership style is to enhance the performance of school teachers. The research method employed in this study is a descriptive qualitative approach with a case study design. The instrument used in this research is a questionnaire in the form of an online Google Form distributed via WhatsApp application. The findings of this research indicate that the path-goal leadership style plays a significant role in improving the performance of teachers at SMAN 1 Patianrowo. Among the four path-goal leadership styles (directive, supportive, participative, and achievement-oriented), the supportive leadership style appears to have a considerable impact on enhancing the performance of school teachers. This suggests that an approach focusing more on support, motivation, and cooperation is the primary preference in enhancing the performance of teachers in SMAN 1 Patianrowo.